Comparative study of multilevel inverters under unbalanced voltage in a single DC link. Issue 8 (1st September 2013) - Maswood, Ali I.; Gabriel, Ooi H. P.; Al Ammar, Essam
Abstract : This study explores the feasibility of an AC/DC/AC drive with near unity power factor front‐end rectifier and five‐level rear‐end multilevel inverter topology with a focus on achieving lower voltage total harmonic distortion and higher energy efficiency. The unity PF front‐end rectifier in this AC/DC/AC drive may cause unbalanced voltage in the DC bus capacitors leading to high voltage distortion on the output AC voltage of a rear‐end multilevel inverter. Based on the analysis, modelling and experimental results, rear‐end multilevel flying‐capacitor inverter with unity PF front‐end rectifier in an AC/DC/AC power drive is proposed which is able to provide better DC voltage balancing when compared to diode‐clamped topology. Having no diode components being used in this multilevel inverter, the flying‐capacitor topology produces lesser commutation losses. Furthermore, rear‐end multilevel flying‐capacitor topology offers better efficiency and good quality output voltage without any bulky and expensive LC filter and even without any additional DC voltage balancing circuitry. The analytical performance of the drive is verified on a 1.3 kW laboratory prototype.